The Cauchy problem for a class of fractional impulsive differential equations with delay - Xiaozhi Zhang (Electronic Journal of Qualitative Theory of Differential Equations, 2012)
In this work, the Cauchy initial value problem is discussed for a class of fractional impulsive differential equations with delay, and the criteria on existence and uniqueness are obtained. Finally, an example is also provided to illustrate the effectiveness of our main results.